The Professional Competence Analysis of Chemistry Teacher of Senior High School in Merauke - Pongkendek, Jesi Jecsen; Marpaung, Dewi Natalia; Ahmar, Dewi Satria; Rahmatia, Sitti (Journal of Applied Science, Engineering, Technology, and Education, 2021)
Teacher competence is the roundness of knowledge, skills and attitudes that manifest smart and responsible actions in carrying out tasks as agents of learning. Teacher competencies consist of pedagogic competencies, social competencies, personality competencies, and professional competencies. This research focuses on teacher professional competence. Teachers' professional competencies are examined in 3 aspects namely mastering the material, mastering basic competencies, and developing learning materials that are creatively influenced. This research is a descriptive study to get a picture of the professional competence of Senior High School chemistry teachers in Merauke District. The study was conducted in 3 schools, namely SMAN 1 Merauke, SMAN 2 Merauke and SMAS YPK Merauke. Data obtained through observation, interviews, and documentation. The data obtained were analyzed by means of data reduction, data presentation and conclusion drawing. Through descriptive data analysis the results are obtained: (a) mastering material with an average value of 1.6 being in the category of very competent; (b) mastering basic competencies with an average value of 1.5 very competent categories; and (c) developing learning materials that are creatively influenced by an average value of 1.25 competent categories. Average overall aspects of professional competence 1.45 competent categories. The results of the analysis indicate the professional competence of chemistry teachers in Merauke District is quite good, although there are things that need to be developed so as to improve the professional competence of teachers who have.